2018
DOI: 10.1002/ijch.201800076
|View full text |Cite
|
Sign up to set email alerts
|

Technology in the Service of Pedagogy: Teaching with Chemistry Databases

Abstract: The chemical sciences integrate numerous pieces of structural data into families of compounds, and countless experimental results of reactive processes into ground rules. Collecting these pieces of information, analyzing them, and making the relevant contextual connections between them is in the heart of chemistry education. Here we emphasize the contribution of technology, and more specifically, chemical databases for enhancing these learning processes. Several important, open access, databases are described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
0
12
0
2
Order By: Relevance
“…It has also been reported that the perception of secondary school students towards the integration of bioinformatics in the curriculum is also very positive in improving their learning (Machluf et al, 2016). Hence, to be scientifically literate with the fast demand of 21 st digital century, it is such a necessity for high school chemistry teachers to upgrade their professional qualifications related to computing technology through professional development on modeling, visualization and application of chemistry and bioinformatics databases in supporting teaching and learning pedagogy (Tuvi-Arad & Blonder, 2019). After the workshop, an increase in awareness, knowledge, and confidence were seen, which could be observed in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that the perception of secondary school students towards the integration of bioinformatics in the curriculum is also very positive in improving their learning (Machluf et al, 2016). Hence, to be scientifically literate with the fast demand of 21 st digital century, it is such a necessity for high school chemistry teachers to upgrade their professional qualifications related to computing technology through professional development on modeling, visualization and application of chemistry and bioinformatics databases in supporting teaching and learning pedagogy (Tuvi-Arad & Blonder, 2019). After the workshop, an increase in awareness, knowledge, and confidence were seen, which could be observed in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Education in the areas of food science, human nutrition and dietetics can utilize the benefits and meet the challenges of the big data era. The potential of Internet databases in teaching chemistry has been recently emphasized by Tuvi-Arad and Blonder [ 67 ]. Databases may serve as tools supporting classic, printed handbooks.…”
Section: Possible Simple Search Schemes To Use For Finding Informamentioning
confidence: 99%
“…Some of these software are provided free of charge with a web-based interface. [8][9][10][11] These features make them easily accessible to non-expert users as well as to chemical educator interested in integrating computational knowledge and skills in the undergraduate chemistry curriculum. [7] Altogether, using computational methods provide opportunities to create an authentic learning experience as students use state-of-the-art research tools and analyze the results of their own calculations rather than relying on published data.…”
Section: Introductionmentioning
confidence: 99%